2015
DOI: 10.1089/cap.2014.0044
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Levels of Second Generation Antipsychotics in Youth: A Systematic Review

Abstract: TDM may be indicated in any circumstance in which cytochrome P450 inhibitors or inducers are coprescribed. Further research is required for establishing a sounder safety profile for SGA use in the pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…Many neuropsychiatric drugs are not approved for use in children or adolescents [416,1308]. To date, therapeutic reference ranges for most neuropsychopharmacological drugs are based upon studies performed in adults, and data about the correlation of concentration with therapeutic response or adverse drug reactions in the paediatric population are scarce [327,1298]. The relative lack of clinical trials and the resultant off-label use could lead to a higher risk of dosing errors and adverse drug reactions.…”
Section: Recommendationmentioning
confidence: 99%
“…Many neuropsychiatric drugs are not approved for use in children or adolescents [416,1308]. To date, therapeutic reference ranges for most neuropsychopharmacological drugs are based upon studies performed in adults, and data about the correlation of concentration with therapeutic response or adverse drug reactions in the paediatric population are scarce [327,1298]. The relative lack of clinical trials and the resultant off-label use could lead to a higher risk of dosing errors and adverse drug reactions.…”
Section: Recommendationmentioning
confidence: 99%
“…It was recently shown that the long-term effectiveness of SGAs in youths needs to be improved, with high rate of clinicians-decided and patients-decided discontinuation [ 92 ]. A possible improvement strategy is to increase our knowledge on therapeutic drug monitoring, but to date empirical information on paediatric populations is scant [ 93 , 94 ]. Close paediatrician-child psychiatrist collaboration should be the first action to achieve this improvement.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on the pharmacokinetics of olanzapine in adolescents; however, a meta-analysis of these studies reported that the data are highly variable, and more research is needed on the pharmacokinetics of olanzapine. 20 The suggested pediatric dose of olanzapine based on the scaling method from the adult dose of 5 mg has varied from 0.06 to 0.13 mg/kg/day. 16,21 The mean dose of olanzapine used in our study was 0.14 mg/kg, which is close to the dose proposed for children.…”
Section: Discussionmentioning
confidence: 99%